Analisa Perpindahan Panas dan Pressure Drop Fluida Nano Al2O3-Air Proses Pendinginan dengan Metode Simulasi - Marali, Aryati Muhaymin; Wahyudi, Slamet; Hamidi, Nurkholis (Jurnal Rekayasa Mesin, 2018)
Conventional heat transfer system is unable to absorb heat well. Various methods have been done to enhance heat transfer. One of them is the methodÂ by using nanofluid which has been done by many researchers; due to the better thermal performances compared to base fluid. The research aims to observe the enhancement of convective heat transfer and pressure drop in the cooling process by using Al2O3 â€“ Water nanofluid. The volume concentration of the Al2O3 varied from 0.2% and 0.3% with 30 nm diameter nanoparticles flowing in a double pipe with the opposite direction. The result showed that the increase of the particle volume concentration leads to enhance convective heat transfer coefficient and pressure drop. The two variables of measurement showed the average heat transfer coefficient increased about 21% with 0.2% and 0.3% volume concentration compared to base fluid. Pressure drop increased about 22.86% with 0.2% and 0.3% volume concentration. In conclusion, the performance of nanofluid slightly increased together with the increase of volume nanofluid concentration.